1999
DOI: 10.1021/jp9918353
|View full text |Cite
|
Sign up to set email alerts
|

Large Nonlinear Refraction and Higher Order Nonlinear Optical Effects in a Novel Organic Dendrimer

Abstract: The fast electronic nonlinear optical (NLO) properties of a novel synthetic organic dendrimer are reported. The complete synthesis of the organic dendrimer is provided. Both the z-scan and self-phase modulation techniques were used to measure the nonlinear refractive index. The magnitude of the nonlinear refractive index (n 2) was measured to be 1.1 × 10 - 4 cm2/GW. The presence of two-photon absorption was observed and the coefficient (β) was found to be 1.2 × 10-2 cm/GW. The nonlinear figure of merit of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 31 publications
0
53
0
Order By: Relevance
“…Synthesis and spectroscopic features of all the structures have been described elsewhere. 8,14 The p-bis͑o-methylstyryl͒-benzene ͓bis-MSB͔ chromophore was used as a model compound for investigations of intermolecular interactions in A-DSB. Solutions in chloroform were used in this study.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis and spectroscopic features of all the structures have been described elsewhere. 8,14 The p-bis͑o-methylstyryl͒-benzene ͓bis-MSB͔ chromophore was used as a model compound for investigations of intermolecular interactions in A-DSB. Solutions in chloroform were used in this study.…”
mentioning
confidence: 99%
“…Optical arrangement for the upconversion experiments has been described previously. [14][15][16] The sample was excited with laser pulses delivered by a frequency doubled output of the Ti:sapphire laser ͑Tsunami, Spectra Physics͒. The laser with an average pulse width of 100 fs tuned at 790-860 nm and a repetition rate of 82 MHz beam was controlled using Berek compensator.…”
mentioning
confidence: 99%
“…It is also interesting to note that the fast nonlinear response was found to be the same for NS1 and CZD4NSC2. 6 From all these results it can be concluded that the complex fluorescence dynamics shown in Figs. 3 and 4 ͑the long-lived decay and the rise-time components͒ is not connected with the formation of excited-state aggregates ͑excimers or exciplexes͒, as was observed for another type of dendrimer molecule composed of phenylene building blocks.…”
Section: Shown Inmentioning
confidence: 78%
“…14 The optical arrangement for the upconversion experiments was described previously. 6,15 The laser source was a Ti:sapphire laser with an average pulse width of 100 fs tuned at 790-860 nm, and a repetition rate of 82 MHz ͑Tsunami, Spectra Physics͒. The sample was excited with light pulses delivered by a frequency-doubled output of the laser at 395-430 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation